Debugging a liver transplant unit. - Finlay, Kylie; Poulton, Cassandra (Transplant Journal of Australasia, 2012)
A project was implemented in the South Australian Liver Transplant Unit (Ward 5E), based at Flinders Medical Centre. The aim of the project was to try and reduce the transmission of vancomycin-resistant enterococci (VRE) following a significant increase in new VRE cases reported on the ward over a six-month period. As both pre- and post-transplant patients are cared for on this ward, a literature search was conducted to assess the risk of VRE colonisation or infection and subsequent outcomes for immunosuppressed patients. A review of all current policies was conducted, several interventions implemented and staff education was increased. Following these interventions, results showed a 70% decrease of Ward 5E-acquired VRE cases.